2015
DOI: 10.1038/ncomms7132
|View full text |Cite
|
Sign up to set email alerts
|

Ambient seafloor noise excited by earthquakes in the Nankai subduction zone

Abstract: Excitations of seismic background noises are mostly related to fluid disturbances in the atmosphere, ocean and the solid Earth. Earthquakes have not been considered as a stationary excitation source because they occur intermittently. Here we report that acoustic-coupled Rayleigh waves (at 0.7–2.0 Hz) travelling in the ocean and marine sediments, retrieved by correlating ambient noise on a hydrophone array deployed through a shallow to deep seafloor (100–4,800 m) across the Nankai Trough, Japan, are incessantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 44 publications
0
11
1
Order By: Relevance
“…We use an ambient noise correlation technique to retrieve waves propagating between two receivers. This technique has been applied to ambient noise records in various wavefields, such as ground motions in seismometer records (Shapiro et al, ), acoustic pressure in water for hydrophone records (Tonegawa et al, ), ultrasonic fields in solids (Lobkis & Weaver, ), and acoustic pressure in air for microbarometer records (Nishida et al, ). Harmon et al () apply the method to ambient noise observed in differential pressure records from the deep seafloor for detecting IGWs.…”
Section: Methodsmentioning
confidence: 99%
“…We use an ambient noise correlation technique to retrieve waves propagating between two receivers. This technique has been applied to ambient noise records in various wavefields, such as ground motions in seismometer records (Shapiro et al, ), acoustic pressure in water for hydrophone records (Tonegawa et al, ), ultrasonic fields in solids (Lobkis & Weaver, ), and acoustic pressure in air for microbarometer records (Nishida et al, ). Harmon et al () apply the method to ambient noise observed in differential pressure records from the deep seafloor for detecting IGWs.…”
Section: Methodsmentioning
confidence: 99%
“…Groos et al (2012) pointed out that such normalization may lead to an amplification of signals generated by temporally persistent and spatially localized sources (e.g. Oliver 1962;Zeng & Ni 2010;Tonegawa et al 2015). Moreover, amplitude normalization tends to favour distant sources compared to local contributions (Tian & Ritzwoller 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The broadband seismometers (Guralp CMG-3T) of DONET were buried 1 m below the seafloor, and have a flat velocity response from 100 Hz to 360 s (e.g., Nakano et al, 2013). The response of the hydrophone decreases from 2 Hz to lower frequencies (e.g., Tonegawa et al, 2015). Also used were the three components of a broadband seismometer deployed in a borehole at a depth of 900 m from the seafloor (Kopf et al, 2011;, at which lower noise levels than those at the seafloor are observed due to the amplitude decay of persistently propagating surface waves.…”
Section: Station Datamentioning
confidence: 99%
“…Waves extracted from seafloor observations are primarily surface waves, including Rayleigh waves, Love waves, their higher modes (e.g., Takeo et al, 2013;Lin et al, 2016;Isse et al, 2019;Kawano et al, 2020), Scholte waves (Mordret et al, 2014), and ocean acoustically-coupled Rayleigh (ACR) waves (Ewing et al, 1957;Sugioka et al, 2001;Butler and Lomnitz, 2002;Butler, 2006). Here, ACR waves (or seismoacoustic modes) can be observed at frequencies of 0.5-5.0 Hz, which include higher modes of Rayleigh waves whose energies are distributed in the ocean and marine sediment, and have a propagation velocity slightly less than 1.5 km/s (Tonegawa et al, 2015). However, teleseismic body waves excited in the ocean areas can be observed at land stations (Gerstoft et al, 2006;Koper et al, 2010;Landès et al, 2010;Gualtieri et al, 2014;Farra et al, 2016;Nishida and Takagi, 2016).…”
Section: Introductionmentioning
confidence: 99%